Short Textbook of Endodontics - Daswani, A. Aarti (Jaypee Brothers Medical Publishers, 2016)
The Short Textbook of Endodontics is an astonishing realization that the field of endodontics has undergone sea changes in the last few years. Endodontic treatment has come a long way from what it was till about two decades ago. Not only dental materials and instruments have become technically superior, but also the concepts, procedures and attitudes of clinicians have acquired a modern outlook. This book contains 34 chapters that focus on dental pulp and the periradicular tissues, morphology and internal anatomy of the root canal system, diseases of the pulp and the periradicular tissues, endodontic microbiology, rationale of endodontic therapy, endodontic access cavity preparation, disinfection of the root canal system, obturation of root canal system, management of discolored teeth, surgical endodontics, pathologic tooth resorption, regenerative endodontics, etc. The Short Textbook of Endodontics has been designed to cover each and every aspect of Endodontics in a concise yet comprehensive manner. Unique feature of this book is inculcating learning through "Mind-maps", a concept introduced. Mind-maps used in this book act as a quick learning aid to the ever-expanding world of endodontics. The general practitioners can use this book to train their mind to remember what next in the course of performing endodontic procedures.